Abstracts of invited presentations at EuroPD congress in Bruges, 2023-11-27 - EuroPD (RDPLF, 2023)
This special issue of the Home Dialysis Bulletin (cross-referenced as Bulletin de la Dialyse à Domicile (BDD)) contains abstracts of guest lectures submitted by the authors. The abstracts are available in English and French. The abstracts of the free communications are available at this link. Many of these abstracts reflect work of particular interest to clinicians and nurses and should be developed into a full article. We, therefore, encourage authors to write a full article and submit it to the BDD at https://www.bdd.rdplf.org if it has not been published or submitted elsewhere. They will be double-blind peer-reviewed and, if accepted, will be published promptly in both languages to ensure the widest possible dissemination. The BDD supports the Diamond Open Access Action Plan and follows its model (Diamond OA scholarly Communication Ecosystem); it is therefore free of charge for authors and readers and accessible to all health professionals and patients.   Ethical considerations: before submitting their abstracts, all authors were informed that their articles would be published in the BDD and translated into French. Authors retain the copyright of their articles. Declaration of interests: Publication of these abstracts is provided free of charge by the French Registry of Peritoneal Dialysis and Home Hemodialysis. No payment or grant has been received from EuroPD or any third party for this work. Copyright: authors retain copyright.